ADSORPSI ASETON, BENZENA, DAN TOLUENA PADA KARBON AKTIF TEMPURUNG KELAPA SEBAGAI PEMBERSIH UDARA RUANG TERTUTUP - Wuntu, Audy (Sam Ratulangi University, 2008)
Adsorption of air pollutant volatile organic compounds, those are acetone, benzene, and toluene onactivated carbon prepared from coconut shell had been studied. The research was aimed to explore theadsorption capacity and adsorption energy of the compounds on coconut shell activated carbon understatic condition. In this condition, the adsorbent was stayed for 24 hours inside a closed bin containingsingle gas: actone, benzene, or toluene. The result showed that the adsorption capacity of thesecompounds on activated carbon was in the order of acetone > benzene > toluene. The same order wasobserved for the parameter of adsorption energy of the compounds on activated carbonÂ Keywords: adsorption, adsorbent, activated carbon, coconut shell